The administrative subcontract: Significance, relevance and implications for intergovernmental relations in China. (January 2016) - Zhou, Li-An
This article attempts to demonstrate the significance, relevance and implications of the 'administrative subcontract' as an analytical framework for understanding China's intergovernmental relations, bureaucratic incentives and administrative governance. As an ideal type, the term 'administrative subcontract' refers to a subcontracting relationship inside the government system, representing a hybrid governance structure between bureaucracy in the Weberian sense and a 'pure' subcontract which occurs among independent entities having no hierarchical relationships. An administrative subcontract exhibits a coherent and consistent set of characteristics along the dimensions of authority relations, economic incentives and internal control. It is argued that these three dimensions are complementary and mutually supportive, and tend to move together if the system encounters systemic shocks. This new framework helps with identifying the key and durable features of China's intergovernmental relations and administrative governance. The notion of the administrative subcontract enables many puzzling observations and patterns regarding the workings of China's government system to be reinterpreted and some important and as yet long understudied issues brought to our attention. The theory of the administrative subcontract is combined with that of 'political tournaments' to extend the analysis of China's political incentives and governance. With regard to vertical subcontracting and horizontal (political) competition inside the government system, an attempt is made to explain the strength and weakness of China's state capacity in various areas of public service.